Environmental Modeling Using MATLAB - Holzbecher, Ekkehard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The book has two aims: to introduce basic concepts of environmental modelling and to faciliate the application of the concepts using modern numerical tools such as MATLAB. It is targeted at all natural scientists dealing with the environment: process and chemical engineers, physicists, chemists, biologists, biochemists, hydrogeologists, geochemists and ecologists. MATLAB was chosen as the major computer tool for modeling, firstly because it is unique in it's capabilities, and secondly because it is available in most academic institutions, in all universities and in the research departments of many companies. In the 2nd edition many chapters will include updated and extended material. In addition the MATLAB command index will be updated and a new chapter on numerical methods will be added.
Part I: Primer to Modeling with MATLAB -- Introduction -- Fundamentals of Modeling, Principles and MATLAB,. Transport -- Transport Solutions -- Transport with Decay and Degradation -- Transport and Sorption -- Transport and Kinetics -- Transport and Equilibrium Reactions -- Ordinary Differential Equations - Dynamical Systems -- Parameter Estimation -- Part II: Advanced Modelling using MATLAB -- Flow Modeling -- Groundwater Drawdown by Pumping -- Aquifer Baseflow and 2D Meshing -- Potential and Flow Visualization -- Streamfunction and Complex Potential -- 2D and 3D Transport Solutions (Gaussian Puffs and Plumes) -- Image Processing and Geo-referencing -- Compartment Graphs and Linear Systems -- Nonlinear Systems -- Graphical User Interfaces -- Numerical Methods - Finite Differences.
Keywords: Environmental sciences; Geography; Engineering mathematics; Environment; Math. Appl. in Environmental Science; Earth Sciences, general; Appl.Mathematics/Computational Methods of Engineering